Visual archeology of platform delivery worker’s subjectivity - De Andrés Arias, Juan (Re-visiones, 2024)
This paper proposes a visual archeology of the rider —delivery platform worker—, a subjectivity produced by platform capitalism and silicolonization. A descriptive analysis of this subjectivity is carried out throughout five pairs of dialectical images —set in dialogue—, dividing the article into five parts: it begins with the description of the context that makes rider subjectivity possible; next, some of the most remarkable features of their problems are exposed, followed by images and statements that refer to other future scenarios from which to frame the contemporary rider subjectivity.